Vertical interaction between village councils, citizen associations, and the municipality: the associations’ perspective - Bavnbæk, Kasper Friis; Thuesen, Annette Aagaard (Politica, 2024)
Based on deliberative democracy theory, this article examines differences between village councils and citizen associations in terms of their interests and interaction with the municipality. Survey data shows that they are engaged with many issues that municipalities are responsible for, and that distance to the municipality’s town hall affects their engagement. Survey data also shows that local councils occupy a position closer to the municipality than citizen associations. The two types of associations are satisfied with their interaction with the municipality but based on different parameters. Regular meetings where the associations have access to direct conversations with politicians and administration and the opportunity to access municipal funds are some of the things that mean most for perceptions of positive interaction.